Residues of Tetracycline, Erythromycin, and Sulfonamides in Beef, Eggs, and Honey from Grocery Stores in Knoxville, Tennessee, USA: Failure of Cooking to Decrease Drug Concentrations - Shamim Sarkar; Stephen A. Kania; Mohamed A. Abouelkhair; Brian Whitlock; Chika C. Okafor (Veterinary Sciences, 2024)
This study evaluated the concentrations of tetracycline, erythromycin, and sulfonamide in beef, eggs, and honey products sold at grocery stores and whether standard cooking to 160 °F (71 °C) reduced the concentrations of antimicrobials spiked into the evaluated food products. In June 2021, the concentrations of selected antimicrobials in 65 samples (8 beef, 48 eggs, 9 honey samples) purchased from grocery stores within Knoxville, Tennessee, were measured using enzyme-linked immunosorbent assays. The Kruskal–Wallis test was used to assess the differences in the median tetracycline concentrations across food types, while the Mann–Whitney test was used to compare the erythromycin residue concentrations between beef and honey. Linear regression was used to analyze whether standard cooking at 160 °F (71 °C) reduced antimicrobial concentrations. Detectable tetracycline concentrations were found in all beef (8/8, 100%), eggs (46/48, 96%), and honey (9/9, 100%) samples, with median concentrations of 7.73, 5.62, and 13.13 µg/kg, respectively. Honey had significantly higher tetracycline concentrations than eggs (p = 0.002). Detectable erythromycin concentrations were found in beef (5/8, 63%) and honey (9/9, 100%), with median concentrations of 0.14 µg/kg for beef and 0.48 µg/kg for honey. None of the antimicrobial concentrations found in the beef and egg products exceeded the U.S. FDA’s maximum residue limits (MRL). Sulfonamide concentrations were undetectable in the beef and egg products. The concentrations of tetracycline, erythromycin, and sulfonamide spiked into the food products did not change significantly in response to cooking to 160 °F (71 °C). The antimicrobial concentrations found in the selected commercial food products were below the MRL, and cooking appeared to not reduce the spiked antimicrobial concentrations in the evaluated food products.